(untitled) - Weber, Nancy D (New York, 1991)
"Has also been published as Journal of gerontological social work, volume 17, numbers 3/4, 1991"--T.P. verso; Includes bibliographical references; Neal A. Newfield, Ph.D., LICSW (Giver)
Keywords: Older blind people -- Services for -- United States; Older blind people -- United States; Older people with visual disabilities -- Services for -- United States; Social work with older people -- United States; Social work with people with disabilities -- United States; Social Work.; Vision Disorders -- in old age.; Công tác xã hội với người lớn tuổi